Andrographolide-encapsulated nanoliposomes with gum Arabic surface modification inhibits cervical cancer growth: In vitro and in silico approaches - Rahmalillah Khairiah; Dwi Hudiyanti; Parsaoran Siahaan; Fadzilah Adibah Abdul Majid; Enny Fachriyah; Nor Hafizah Zakaria (Results in Chemistry)
Cervical cancer is still the most common cause of cancer-related deaths among women globally, despite improvements in screening and treatment. Although andrographolide (AND), a substance with significant anticancer properties, shows promise, its poor solubility and stability limit its usefulness in treating cervical cancer. This study used coconut liposomes (CL) modified with gum Arabic (GA) to create and optimize a liposomal formulation for AND in order to overcome these difficulties. Important parameters were evaluated, including drug release (DR), particle size (PS), zeta-potential (ζ-potential), encapsulation efficiency (EE), and liposomal morphology. High EE (87.7 % for CLAND and 92.9 % for CLANDGA) and suitable PS (66.2 nm for CLAND and 92.6 nm for CLANDGA) were shown by the optimised formulations, AND-loaded nanoliposomes (CLAND) and AND-loaded nanoliposomes modified with GA (CLANDGA). After GA was added, the ζ-potential readings showed good stability. The liposomes had a spherical shape with regulated DR (∼37 % over 72 h). The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenylte-trazolium bromide (MTT) experiment revealed that encapsulated AND inhibited HeLa cervical cancer cells more in comparison to free AND. Strong contact was shown by the docking score and binding energy of AND binding to the HPV 18B E6 receptor, which were determined by molecular docking and dynamic simulations to be −6.72 kcal/mol and − 90.002 kJ/mol, respectively. All things considered, this study highlights the possibility of employing AND encapsulated in nanoliposomes to successfully regulate the proliferation of cervical cancer cells.